On the existence of AgM9(VO4)6I (M = Ba, Pb). Issue 77 (17th October 2017) - Johnstone, E. V.; Bailey, D. J.; Stennett, M. C.; Heo, J.; Hyatt, N. C.
Abstract : Attempts to synthesize "AgM9 (VO4 )6 I" (M = Ba, Pb), potential waste form materials for radioiodine, were unsuccessful, demonstrating that AgI incorporation into an iodine-deficient apatite phase is not feasible under the reported conditions. Abstract : The syntheses of the reported compounds AgM9 (VO4 )6 I (M = Ba, Pb) were reinvestigated. Stoichiometric amounts of AgI with either M3 (VO4 )2 (M = Ba, Pb) or PbO and V2 O5 were reacted in the solid-state at elevated temperatures in air or in flame-sealed quartz vessels. The resulting products were characterized by X-ray diffraction, scanning electron microscopy with energy dispersive X-ray analysis, and thermal analyses. Results show that, for all reaction conditions, the target AgM9 (VO4 )6 I (M = Ba, Pb) phases could not be isolated. Instead, heterogeneous phase distributions of primarily M3 (VO4 )2 (M = Ba, Pb) and AgI were obtained. These findings demonstrate that AgI incorporation into single phase, iodine-deficient apatite derivatives for the immobilization of iodine-129 are not feasible under such conditions. This conclusion is important for the conditioning of iodine-129 in advanced reprocessing flowsheets, where iodine is typically sequestered as AgI.